2012
DOI: 10.1063/1.4716027
|View full text |Cite
|
Sign up to set email alerts
|

A monoclinic-tetragonal ferroelectric phase transition in lead-free (K0.5Na0.5)NbO3-x%LiNbO3 solid solution

Abstract: A monoclinic-tetragonal ferroelectric phase transition in lead-free (K 0.5 Na 0.5 )NbO 3 -x%LiNbO 3 solid solution A monoclinic ferroelectric phase with space group Pm has been discovered in lead-free (K 0.5 Na 0.5 )NbO 3 -5%LiNbO 3 solid solution ceramics by high energy synchrotron x-ray powder diffraction measurements. At ambient temperature, the lattice parameters of this monoclinic structure were (a m , b m , c m ; b) ¼ (4.015 Å , 3.944 Å , 3.987 Å ; 90.34 ). This monoclinic phase transformed to a tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 62 publications
5
38
0
Order By: Relevance
“…This agrees well with the recently reported observation by high energy synchrotron XRD diffraction measurements of the local structure of monoclinic symmetry in KNN ceramics. 40 In this last case, also the more relevant phase is the T phase. As a consequence, the most probable origin of this behaviour must be related to the solubility of Sb 5+ ions into the perovskite structure.…”
Section: Resultsmentioning
confidence: 97%
“…This agrees well with the recently reported observation by high energy synchrotron XRD diffraction measurements of the local structure of monoclinic symmetry in KNN ceramics. 40 In this last case, also the more relevant phase is the T phase. As a consequence, the most probable origin of this behaviour must be related to the solubility of Sb 5+ ions into the perovskite structure.…”
Section: Resultsmentioning
confidence: 97%
“…[3][4][5] Since Saito et al 6 have demonstrated that the KNN ceramics modified with Li, Ta, or Sb exhibit sufficient piezoelectric properties comparable to commercially available PZT-based ceramics, considerable interests have been devoted to improve the piezoelectric properties of KNN ceramics. [7][8][9][10][11] Doping is a mandatory solution to tailor the properties of KNN for specific applications. For Mn-doped KNN and KNN based ceramics, the improved electrical properties were observed.…”
Section: Introductionmentioning
confidence: 99%
“…4 One of the most promising alternatives is the (K 0.5 Na 0.5 )NbO 3 (KNN)-based solid solution system. [5][6][7][8][9][10][11] Various chemical modifiers, such as LiTaO 3 , 12,13 LiNbO 3 , [14][15][16] and LiSbO 3 , 17,18 have been employed to facilitate processing and optimize the piezoelectric behavior. The enhanced piezoelectricity in these compositionally modified KNN-based oxides is a result of reducing the temperature of the polymorphic phase boundary (PPB), where the tetragonal and orthorhombic phases coexist, from $210 C, for unmodified KNN, to near room temperature.…”
Section: Introductionmentioning
confidence: 99%